Functional Subsets of the VirB Type IV Transport Complex Proteins Involved in the Capacity of Agrobacterium tumefaciens To Serve as a Recipient in virB-Mediated Conjugal Transfer of Plasmid RSF1010 - Liu, Zhenying (American Society for Microbiology, 2003)
The virB-encoded type IV transport complex of Agrobacterium tumefaciens mediates the transfer of DNA and proteins into plant cells, as well as the conjugal transfer of IncQ plasmids, such as RSF1010, between Agrobacterium strains. While several studies have indicated that there are physical interactions among the 11 VirB proteins, the functional significance of the interactions has been difficult to establish since all of the proteins are required for substrate transfer. Our previous studies, however, indicated that although all of the VirB proteins are required for the capacity of a strain to serve as an RSF1010 donor, only a subset of these proteins in the recipient is necessary to increase the conjugal frequency by 3 to 4 logs. The roles of particular groups of VirB proteins in this increased recipient activity were examined in the study reported here. Examination of the expression of subgroups of virB genes revealed that translation of virB6 is necessary for expression of downstream open reading frames. Expression of limited subsets of the VirB proteins in a recipient strain lacking the Ti plasmid revealed that the VirB7 to VirB10 proteins yield a subcomplex that is functional in the recipient assay but that the VirB1 to VirB4 proteins, as a group, dramatically increase this activity in strains expressing VirB7 to VirB10. Finally, the membrane distribution and cross-linking patterns of VirB10, but not of VirB8 or VirB9, in a strain expressing only VirB7 to VirB10 are significantly altered compared to the patterns of the wild type. These characteristics are, however, restored to the wild-type status by coexpression of VirB1 to VirB3. Taken together, these results define subsets of type IV transport complex proteins that are critical in allowing a strain to participate as a recipient in virB-mediated conjugal RSF1010 transfer.